2016
DOI: 10.1049/hve.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of streamer discharges in liquids: a review

Abstract: Streamer discharges in liquids have received lots of attention with respect to their considerable applications in various disciplines. Much effort has been spent to understand the basis of streamer ignition and propagation in dielectric liquids, but a comprehensive mechanism is far from conclusive. In this review, based on an introduction to the streamer physics and experimentally observed characteristics in various liquids, the authors emphasise on the current status of streamer discharge ignition mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 72 publications
(94 reference statements)
0
75
0
Order By: Relevance
“…Research in [12,29,30] suggested that both electronic and gaseous processes at streamer tips are responsible for the development of fast streamers. In addition, streamer propagation models shown in Figure 12 indicated that charge splitting process is dominant for the branching of dark channels, whereas charge amplification process is dominant for the branching of bright channels.…”
Section: Fast Negative Streamers Versus Fast Positive Streamers: Diffmentioning
confidence: 99%
“…Research in [12,29,30] suggested that both electronic and gaseous processes at streamer tips are responsible for the development of fast streamers. In addition, streamer propagation models shown in Figure 12 indicated that charge splitting process is dominant for the branching of dark channels, whereas charge amplification process is dominant for the branching of bright channels.…”
Section: Fast Negative Streamers Versus Fast Positive Streamers: Diffmentioning
confidence: 99%
“…A brief review of the mechanisms of formation of streamer discharges in a liquid [8] mentions the influence of molecular ionization and ion dissociation factors, which depends on the electric field, Auger mechanism, accompanying the electric breakdown mechanism.…”
mentioning
confidence: 99%
“…, (8) where В, с are the empirical constants that depend on the composition of the gas inside the bubble (for example, for water vapor at Е/р = 120 -800 (V•m)/N constants B = 290, c = 0.3 -0.6); p 0 is the normal atmospheric pressure, p 0 ≈ 10 5 Pa; h = r 2 /r 1 ; d cr is the critical (minimal) size of the bubble at which its breakdown occurs determined according to (9): The calculation according to formula (8) assumes the following assumptions:…”
mentioning
confidence: 99%
“…Gas–liquid cold plasma is a new branch of cold plasma, and has been adopted to treat waste water, produce ammonia, sterilize the bacteria, and fabricate nanomaterials . Different from plasma in the gas phase, electron‐induced reactions may take place at the gas–liquid interface in gas–liquid plasma . The products in gas–liquid plasma may undergo two pathways: one is to escape from the gas–liquid interface to the gas phase, and the other is to remain in the liquid phase to cause relevant liquid‐based chemical reactions.…”
mentioning
confidence: 99%
“…However, the values were calculated without considering the electrons. Plasma synthesis may make many reactions become possible or more quickly with the assistance of energetic electrons . Equation is an exothermic reaction, which consumes the OH − ions generated by the former reaction to form the Cu 2 (OH) 3 NO 3 .…”
mentioning
confidence: 99%